The Effect of Cold Stress on the Gastric Mucosa of Adult Male Albino Rats: A Light Microscope Study - Ghada A. Abdel-Hamid,; Rana A. Beshbishy,; Afrah A. Al-Awa,, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Cold stress affects the human body systems especially respiratory, cardiovascular and gastrointestinal systems. An evaluation performed on the structural changes that occurred in the gastric mucosa of adult rat induced by cold exposure under laboratory conditions. In this study, twenty adult male albino rats were divided into two groups: A control group placed in room temperature (25oC), and an experimental group exposed for two hours to the cold weather (8oC). Results revealed that cold exposure induced shrinkage and increase of the mucosal folds, in addition to disruption, destruction of epithelial cells, which line these folds. Moreover, it resulted in increase secretions of gastric glands with loss of its normal architecture. Also notice, a marked congestion and a cellular infiltration of the mucosa. Hence, concluded that cold exposure affected gastric mucosa of the stomach that may lead to gastric ulcer on prolonged cold exposure.